1999
DOI: 10.1089/acm.1999.5.135
|View full text |Cite
|
Sign up to set email alerts
|

Use of Noninvasive Electroacupuncture for the Treatment of HIV-Related Peripheral Neuropathy: A Pilot Study

Abstract: The results support the hypothesis that low-voltage electroacupuncture will improve the condition of the neuropathic HIV/AIDS patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 14 publications
0
21
0
2
Order By: Relevance
“…These investigations have shown positive clinical effects, how ever, most studies are still challenged by small sample sizes, difficulties with blinding, standardisation and poor iso lation of treatment, due to the nature of treating HIV. (Fulk et al, 2004;Galantino et al, 1999;Posner et al, 2004;Shor Posner et al, 2004;Worthington et al, 2005). Incorporation into teaching should therefore take cognisance of the levels of evidence.…”
Section: Applying Mainstreaming Principlesmentioning
confidence: 99%
“…These investigations have shown positive clinical effects, how ever, most studies are still challenged by small sample sizes, difficulties with blinding, standardisation and poor iso lation of treatment, due to the nature of treating HIV. (Fulk et al, 2004;Galantino et al, 1999;Posner et al, 2004;Shor Posner et al, 2004;Worthington et al, 2005). Incorporation into teaching should therefore take cognisance of the levels of evidence.…”
Section: Applying Mainstreaming Principlesmentioning
confidence: 99%
“…Some studies have examined the effect of acupuncture on HIV-associated neuropathic pain, but the results are inconsistent. [33][34][35] In one prospective study 33 evaluating acupuncture for the treatment of HIV/acquired immunodeficiency disease patients with antiretroviral drug-induced neuropathy, noninvasive skin electrodes were placed on leg acupuncture points BL60, ST36, K1, and LIV3. Low-frequency current was applied for 20 minutes every day for 30 days.…”
Section: Acupuncture In the Treatment Of Neuropathy And Neuropathic Painmentioning
confidence: 99%
“…Tables 5 and 7 Butters et al (1993) To compare the views of palliative care reported by patients, informal carers and the community care team, a multidisciplinary team caring for people with late stage HIV/AIDS illness. Galantino et al (1999) To evaluate the effect of electroacupuncture in improving the condition of neuropathic HIV/AIDS patients Hardy et al (1999) To assess the quality of life of patients in palliative care by using the Rotterdam Symptom Checklist (2002) To evaluate information about the variability in the documentation and the services among the palliative care units and on factors influencing this variability Goodwin et al (2003) To evaluate the effectiveness of palliative day care in improving pain, symptom control, and quality of life herbal formulation, cognitive behavioural group therapy (CBT) and peer support/ counselling group therapy (PSC) used in palliative care in improving the quality of life of patients. The findings demonstrate that complementary or alternative therapies such as massage therapy, CBT and PSC were effective in palliative care.…”
Section: Observational Studymentioning
confidence: 99%